Energy Audit and Energy Efficiency Improvement Proposal for Pejabat Pembangunan dan Penyenggaraan (PPP), UTHM - Asri, Ikhwan; Abd Rahman, Ramhuzaini (Research Progress in Mechanical and Manufacturing Engineering, 2026)
Since Malaysia’s building industry contributes significantly to the country’s energy consumption, energy efficiency is a top national concern. The Sustainable Energy Management System (SEMS) is presently being implemented by Universiti Tun Hussein Onn Malaysia (UTHM) in order to enhance its energy performance. This study focuses full on carrying out an energy audit at the Pejabat Pembangunan dan Penyenggaraan (PPP) building, where issues with inefficient and unmonitored energy usage have been found. This study evaluates the energy consumption patterns of the PPP building and investigates major inefficiencies across key systems, including lighting, and MVAC system. The data were collected through a walkthrough audit and the UTHM energy monitoring system known as ENERGY SCADA. The walkthrough audit provided information on equipment type, operating conditions, and usage behavior, while the SCADA system supplied real-time measurements of power, cost, and energy trends throughout the year. Analysis of the data collected helps to reveal the building’s energy consumption and overall energy performance. The result from the audit indicates opportunities for improvement and the unnecessary energy consumption. This study supports PPP’s efforts to improve operational efficiency by identifying consumption trends, inefficiencies, and possible low-cost or high-impact alternatives. The PPP Building Energy Index (BEI) is 74.20 kWh/m2/year below than the standard of MS 1525:2019. This indicate PPP energy consumption is not exceed the standard. The findings of PPP BEI also support UTHM’s larger sustainability objectives in reducing energy consumption systematically and act as a baseline for upcoming energy audits in UTHM.